A Lack of Effectiveness in the ATM-Orchestrated DNA Damage Response Contributes to the DNA Repair Defect of HPV-Positive Head and Neck Cancer Cells - Köcher, Sabrina; Zech, Henrike Barbara; Krug, Leonie; Gatzemeier, Fruzsina; Christiansen, Sabrina; Meyer, Felix; Rietow, Ruth; Struve, Nina; Mansour, Wael Yassin; Kriegs, Malte; Petersen, Cordula; Betz, Christian; et al. (Frontiers in Oncology, 2022)
Patients with human papillomavirus-positive squamous cell carcinoma of the head and neck (HPV+ HNSCC) have a favorable prognosis compared to those with HPV-negative (HPV-) ones. We had shown previously that HPV+ HNSCC cell lines are characterized by enhanced radiation sensitivity and impaired DNA double-strand break (DSB) repair. Since then various publications suggested a defect in homologous recombination (HR) and dysregulated expression of DSB repair proteins as underlying mechanisms but conclusions were often based on very few cell lines. When comparing the expression levels of suggested proteins and other key repair factors in 6 HPV+ vs. 5 HPV- HNSCC strains, we could not confirm most of the published differences. Furthermore, HPV+ HNSCC strains did not demonstrate enhanced sensitivity towards PARP inhibition, questioning a general HR defect. Interestingly, our expression screen revealed minimal levels of the central DNA damage response kinase ATM in the two most radiosensitive HPV+ strains. We therefore tested whether insufficient ATM activity may contribute to the enhanced cellular radiosensitivity. Irrespective of their ATM expression level, radiosensitive HPV+ HNSCC cells displayed DSB repair kinetics similar to ATM deficient cells. Upon ATM inhibition, HPV+ cell lines showed only a marginal increase in residual radiation-induced γH2AX foci and induction of G2 cell cycle arrest as compared to HPV- ones. In line with these observations, ATM inhibition sensitized HPV+ HNSCC strains less towards radiation than HPV- strains, resulting in similar levels of sensitivity. Unexpectedly, assessment of the phosphorylation kinetics of the ATM targets KAP-1 and Chk2 as well as ATM autophosphorylation after radiation did not indicate an obvious difference between HPV+ and HPV- HNSCC cells. Furthermore, ATM inhibition delayed radiation induced DNA end resection in both HPV+ and HPV- cells to a similar extent, suggesting comparable functionality. In conclusion, DNA repair kinetics and a reduced effectiveness of ATM inhibition clearly point to an impaired ATM orchestrated DNA damage response in HPV+ HNSCC cells but since ATM itself is apparently functional the molecular mechanisms need to be further explored.